2020
DOI: 10.1186/s43044-020-00089-7
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous trans-ulnar versus trans-radial arterial approach for coronary angiography and angioplasty, a preliminary experience at an Egyptian cardiology center

Abstract: Background Trans-ulnar approach was proposed primarily for elective procedures in patients not suitable for trans-radial approach that was introduced two decades ago. The trans-ulnar approach is as safe and effective as the trans-radial approach for coronary angiography and intervention. Aim This study’s aim was to assess the feasibility and safety of the trans-ulnar approach in coronary procedures as a preliminary experience for operators experienced in trans-radial approach with no/minimal trans-ulnar appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…We found minor bleeding in 28 (23.7%) patients followed by ulnar artery occlusion, excessive bleeding, ulnar nerve injury and hematoma in 10 (8.5%), 8 (6.8%), 6 (5.08%) and 2 (2.5%) patients respectively. These results were comparable to some previous studies [18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found minor bleeding in 28 (23.7%) patients followed by ulnar artery occlusion, excessive bleeding, ulnar nerve injury and hematoma in 10 (8.5%), 8 (6.8%), 6 (5.08%) and 2 (2.5%) patients respectively. These results were comparable to some previous studies [18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…In our study we found that 76 (64.41%) patients had stable angina, 26 (22.03%) patients had unstable angina and 16 (13.56%) patients had STEMI. These results were comparable to the studies previously conducted [17][18]. In this study we found no major complications associated to transulnar approach.…”
Section: Discussionsupporting
confidence: 92%
“…While, in the previous study 2020 (8) , the mean fluoroscopy time in the ulnar group was 5.6 ± 1.9 min for CA and 12.4 ± 2.6 min for PCI, whereas in the radial group it was 5.3 ± 2.1 min for CA and 11.9 ± 2.3 min for PCI. However, none of these differences reached statistical significance (p > 0.05).…”
Section: Discussionmentioning
confidence: 64%
“…Heparin and intraarterial vasodilators (nitroglycerin and verapamil) were administered, in addition to cardiac catheterization. Following catheterization, the sheath was extracted, and a compressive dressing was utilized to achieve hemostasis (8) . Ulnar Artery Puncture Variations: When ulnar artery pulsations are weak but palpable at the distal wrist, it is considered safe to indentify the ulnar artery further distally, at the level of skinfolds over the carpal bones.…”
Section: Ulnar Artery Puncturementioning
confidence: 99%
“…While there have not been many studies comparing trans-ulnar with trans-radial approach, a trans-ulnar approach is described as an alternative to trans-radial access 20. In randomized studies for coronary interventions, complication risks using trans-ulnar access were found to be close to trans-radial access 21 22. Therefore, success in deploying the Xience Skypoint using three different approaches demonstrate the stent’s flexibility, which gives providers the ability to perform their cases in a way that will be most beneficial to their patients.…”
Section: Discussionmentioning
confidence: 99%